Role of Information Technology to Control Corruption on Local Government in Nepal - Pant, Lalit (DMC Research Journal, 2023)
Information Technology is very powerful tool to reduce corruption, increase the transparency & accountability and develop the nation in today's world. This study describes the role of IT in local government for accountability, transparency & corruption control. Improvement of delivery service mechanism, open government, administrative reform, law enforcement and social capital through information technology can provide accountability, efficiency, transparency to the public. This study is focused on local governments of Nepal. Corruption, lack of transparency, accountability & efficiency are the main problem for development of local society in local governments. To reduce these types of problem IT can play vital role. The main aim of this study is to explore the current status of information technology and its use in local governments. The researcher has applied field survey, direct interview and observation method to collect primary data from employees, public and elected representative body of local governments for currents status and utilization of IT. The researcher has analyzed current status of IT and its utilization by their employees, public & elected representative for different activities in local governments then concludes impacts of it on transparency, accountability & control corruption in local governments. Overall proper implementation of Information Technology played vital role to increase the accountability, transparency and efficiency of work by delivering quick service and other activities in local governments and reduce the corruption & develop the society of local governments.